2019
DOI: 10.1111/itor.12701
|View full text |Cite
|
Sign up to set email alerts
|

Balancing product differentiation and cost saving in the presence of consumer deliberation

Abstract: This paper investigates the manufacturer's optimal product line design under different production strategies when customers with different preference structures (dominating or nondominating) need to incur the deliberation cost to uncover customers' valuations of product quality. We characterize the optimal price, quality, and profit under different production strategies and preference structures. Our results demonstrate that the optimal product line under both production strategies is threshold-controlled, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Some literature considered differentiated product design, including vertical differentiation (quality or function difference) and horizontal differentiation (same quality, different styles or tastes). Because product differentiation has additional production costs, some papers weighed component commonality and product differentiation (Desai et al, 2001;Heese and Swaminathan, 2011;Kim et al, 2013;Xu and Zhou, 2021). Lacourbe et al (2009) studied the differentiated product design of monopoly companies and found horizontal differentiation brings major profits, and vertical differentiation brings marginal benefits.…”
Section: Technology Research and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature considered differentiated product design, including vertical differentiation (quality or function difference) and horizontal differentiation (same quality, different styles or tastes). Because product differentiation has additional production costs, some papers weighed component commonality and product differentiation (Desai et al, 2001;Heese and Swaminathan, 2011;Kim et al, 2013;Xu and Zhou, 2021). Lacourbe et al (2009) studied the differentiated product design of monopoly companies and found horizontal differentiation brings major profits, and vertical differentiation brings marginal benefits.…”
Section: Technology Research and Developmentmentioning
confidence: 99%
“…Some literature considered R&D at the product level (Hong and Guo, 2019;Agi and Yan, 2020;Wang et al, 2021). Some others considered component R&D, but assumed that the manufacturers cooperate in R&D (Kim et al, 2013;Xu and Zhou, 2021). We explore whether the manufacturer develops components when the market is mature and the supplier can provide components.…”
Section: Technology Research and Developmentmentioning
confidence: 99%
“…(2018) focus on innovation investment to improve energy efficiency and the impact of cost sharing between a manufacturer and retailer. Xu and Zhou (2019) investigate the manufacturer's product line decisions when they can invest in some innovative items to improve customers’ valuation of product quality. Feng (2019) studies an inventory replenishment model with dynamic pricing and innovation investment for perishable products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the research methodology, with the unique explanatory power and wide applicability, sequential games have been used by numerous researchers to investigate games among market players with different economic backgrounds (Chen et al, 2021; Chen, Xie, & Liu, 2020; Xu & Zhou, 2020). Bagwell and Staiger (1999, 2002) showed that designing trade policy can solve the prisoner's dilemma caused by terms of trade in standard competition.…”
Section: Introductionmentioning
confidence: 99%